Recent progress on quantum frequency standards at BIRMM - Xue, Xiaobo; Zhou, Tiezhong; Wang, Nuanrang; Zhang, Shengkang; Ge, Jun (Frontiers in Physics, 2022)
Quantum frequency standards are crucial for time measurement, satellite navigation, telecommunication and other important application fields. Beijing Institute of Radio Metrology and Measurement (BIRMM) has been working on quantum frequency standards and their applications for tens of years. In this paper, the latest progress on quantum frequency standards at BIRMM is introduced, including a calcium optical clock, an active hydrogen clock and a mercury ion microwave clock. Based on the 1S0-3P1 transition of calcium atoms, a transportable optical clock prototype is built, which shows a stability of 8E-15/1s. A compact active hydrogen maser is developed for the Chinese space station. It is going to be used for scientific researches such as examining the theory of general relativity of Einstein and is about to be launched later this year. The preliminary frequency stability of the maser is 1.27E-15/10000s. In addition, a mercury ion microwave clock prototype using the hyperfine transition between 62S1/2, F = 0 & 62S1/2, F = 1 is also developed. The trapped Hg+ ions are pumped by mercury discharge lamps and cooled by Helium gas. The measured clock transition linewidth is about 1 Hz, and a frequency stability of 4E-13/1s and 4E-14/1000s is achieved.